A comparative study of canine epididymal sperm collection techniques and cryopreservation - Ali Hassan, Hiba; Banchi, Penelope; Domain, Guillaume; El Khoury, Rosemary; Chaaya, Rana; Wydooghe, Eline; Smits, Katrien; Van Soom, Ann (Frontiers in Veterinary Science, 2023)
An optimized collection method and freezing protocol for preservation of epididymal spermatozoa remains a topic of interest to many scientists. The current study focused on the collection and preservation of canine epididymal spermatozoa. During the process of collection of canine epididymal spermatozoa, blood content can occur, which may affect sperm cryopreservation in a negative way. Here, we compared first two epididymal sperm collection techniques (epididymal mincing (EM) and single incision epididymal sperm aspiration (SESA)); and next we tried to solve the issue of blood content using an erythrocyte lysis buffer (ELB). Hence spermatozoa were collected after weighing the epididymides, either by EM or SESA, and sperm quality assessed prior to and post freezing (concentration, total sperm output (TSO), motility, viability and morphology). Next, new sperm samples were collected from eight epididymides by EM and subjected either to a standard freezing protocol or to an ELB treatment freezing protocol. Post-thaw sperm parameters (concentration, TSO, motility, viability and morphology), including intracellular reactive oxygen species (ROS) and lipid peroxidation were assessed. The correlation between the weight of the epididymis and the TSO was evaluated based on the collection technique, and differences in sperm parameters were detected both within different collection techniques and between different pre-freezing treatment protocols. There was a very strong correlation between the weight of the epididymis and the TSO for the EM technique (P = 0.002, R2 = 0.6), along with an increased sperm motility with EM compared to SESA (median 80%, inter-quartile range (IQR) 88-65 and median 67.5%, IQR 72.5-52.5, respectively; P=0.002). Post-thaw samples subjected to ELB treatment freezing protocol had lower motility and higher intracellular ROS compared to the standard freezing protocol (motility: median 56.25%, IQR 60-48.75 and median 70%, IQR 72.5-63, respectively; P=0.01; ROS: median 78.5%, IQR 81.25-75.5 and median 70%, IQR 70.5-68.75, respectively; P=0.04). The results indicated that EM is a better technique to harvest epididymal spermatozoa despite the presence of some blood content. Furthermore, the ELB treatment should not be implemented to remove those red blood cells prior to cryopreservation of epididymal spermatozoa in dogs.